Not as simple as ABC: Tools to trigger massive transfusion in pediatric trauma. Issue 2 (16th February 2022) - Phillips, Ryan; Shahi, Niti; Acker, Shannon N.; Meier, Maxene; Shirek, Gabrielle; Stevens, Jenny; Recicar, John; Moulton, Steven; Bensard, Denis
Abstract : BACKGROUND: Early and accurate identification of pediatric trauma patients who will receive massive transfusion (MT) is not well established. We developed the ABCD (defined as penetrating mechanism, positive focused assessment with sonography for trauma, shock index, pediatric age-adjusted [SIPA], lactate, and base deficit [BD]) and BIS scores (defined as a combination of BD, international normalized ratio [INR], and SIPA) and hypothesized that the BIS score would perform best in the ability to predict the need for MT in children. METHODS: Pediatric trauma patients (≤18 years old) admitted to our trauma center between 2008 and 2019 were identified. Using a receiver operator curve, we defined cutoff points for lactate (≥3.2), BD (≤−6.9), and INR (≥1.4). ABCD scores were calculated by combining penetrating mechanism; positive focused assessment with sonography for trauma examination; SIPA; lactate; and BD. BIS scores were calculated by combining BD, INR, and SIPA. The sensitivity, specificity, and accuracy of each score were calculated based on receiving MT. RESULTS: Seven hundred seventy-two patients were included, of which 59 (7.6%) underwent MT. The best predictor of receiving MT was achieved by a BIS score of ≥2 that was 98% sensitive and 23% specific with an area under the curve of 0.81. The ABCD score of ≥2 was 97% sensitive and 20% specific with an area under the curve of 0.77. CONCLUSION: The BIS score, which takes into account derangements in acidosis, coagulopathy, and SIPA, is accurate and easy to perform and can be incorporated into a simple bedside screening tool for triggering MT in pediatric trauma patients. LEVEL OF EVIDENCE: Diagnostic Tests or Criteria, Level IV.